GENDER INEQUALITIES AND SMOKING IN BRAZILIAN PEOPLE 50 YEARS OR MORE: Gender Inequality in Brazilian Smokers - do Amaral Júnior, Orlando Luiz; Braccini Fagundes , Maria Laura; Rissotto Menegazzo , Gabriele; Melgarejo do Amaral Giordani , Jessye (Journal of Health Care, 2021)
BACKGROUND: Smoking is a risk factor responsible for the large number of deaths in South American countries, being an important risk factor for the occurrence of chronic non-communicable diseases, especially circulatory diseases. In addition, the unfair and avoidable inequalities derived from social position, roles and expectations between men and women in society are evident and can influence smoking. OBJECTIVES: Was to estimate the differences between socioeconomic and demographic factors associated with smoking independently between Brazilian men and women over the age of 50 years. METHODS: This is a cross-sectional study, composed of 9,412 individuals. Demographic and socioeconomic factors were collected through individual and household questionnaires in 2015. Prevalence ratios were obtained using multivariate Poisson regression. RESULTS: Women living in rural areas had a 35% lower prevalence of smoking than those living in urban areas. It was also observed that women with a higher education level than 12 years of university study had a 28% lower prevalence when compared to those who studied up to 3 years. In both cases, men were not statistically associated CONCLUSIONS: It is suggested that public health policies should consider gender equity as a criterion for implementing policies aimed at reducing smoking.